FORMING OF SOCIAL TRUST OF LOCAL COMMUNITY BY MEANS OF SOCIAL PRACTICIES - O. P. Zvonkina (Дискурс)
The aim of the article is to answer the question about the possibility of leveling trust using effective social practices in the local community. For the purposes of the article functioning of social trust is revealed in the local community, a comparison of micro-, meso- and macro levels of trust functioning is performed. It was concluded that trust prevails at the micro- and macro levels and its redistribution is possible to the meso-level by means of social practices.